Réponses

  • Omnes
  • Modérateur confirmé
2014-02-18T22:09:32+01:00
Salut,

I= (2x-3)²-(5x-7)(2x-3)
I = (4x² - 12x + 9) - (10x² - 15x - 14x + 21)
I = 4x² - 12x + 9 - 10x² + 29x -21
I = -6x² +17x -12


I= (2x-3)²-(5x-7)(2x-3)
I = (2x-3)(2x-3) - (5x-7)(2x-3)
I = (2x-3)[(2x-3) - (5x-7)]
I = (2x-3)(2x - 3 -5x + 7)
I = (2x-3)(-3x +4)

Pour x = 0:

I = (2*0-3)(-3*0 +4)
I = -3 * 4
I = -12

Pour x = 3/2

I = (2x-3)(-3x +4)\\
I = (2* \frac{3}{2} - 3)(-3* \frac{3}{2}  + 4)\\
I = (3-3)( \frac{9}{2} +4)\\
I = 0


Bonne soirée !